Adjuvant Therapy for Stage IB Germ Cell Tumors: One versus Two Cycles of BEP - Robert A. Huddart; Alison M. Reid (Advances in Urology)
Testicular germ cell tumours are the commonest tumours of young men and are broadly managed either as pure seminomas or as ‘nonseminomas’. The management of Stage 1 nonseminomatous germ cell tumours (NSGCTs), beyond surgical removal of the primary tumour at orchidectomy, is somewhat controversial. Cancer-specific survival rates in these patients are in the order of 99% regardless of whether surveillance, retroperitoneal lymph node dissection, or adjuvant chemotherapy is employed. However, the toxicities of these treatment modalities differ. Undertreating those destined to relapse exposes them to the potentially significant toxicities of 3-4 cycles of bleomycin, etoposide, and cisplatin (BEP) chemotherapy. Conversely, giving adjuvant chemotherapy to all patients following orchidectomy results in overtreatment of a significant proportion. Therefore, the challenge lies in delineating the patient population who require adjuvant chemotherapy and in determining how much chemotherapy to give to adequately reduce relapse risk. This chapter reviews the factors to be considered when adopting a risk-adapted strategy for giving adjuvant chemotherapy in Stage 1B NSGCT sand discusses the data regarding the number of BEP cycles to administer.